Properties of Washed Human Platelets - Kinlough-Rathbone, Raelene L; Fraser Mustard, J; Packham, Marian A; Perry, Dennis W; Reimers, Hans-Joachim; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1977)
We have shown previously that washed human platelets resuspended in Tyrode solution containing albumin and apyrase maintain their disc shape and their ability to aggregate upon the addition of low concentrations of ADP, providing fibrinogen is added to the suspending medium. We have now examined their responses to other aggregating and release-inducing agents. Collagen, arachidonate, thrombin, immune serum globulin, the ionophore A 23, 187 and phytohaemagglutinin from Phaseolus vulgaris caused aggregation and release of granule contents. The response to adrenaline was variable. Serotonin caused the platelets to change shape but no aggregation or release occurred. Addition of a small amount of plasma was necessary for ristocetin-induced aggregation. Polylysine caused immediate platelet-to-platelet adherence with little or no release of granule contents. Responses to collagen or thrombin were greater in a modified medium containing magnesium but no calcium; in this medium, aggregation caused by ADP or polylysine was followed by the release of granule contents whereas these agents caused aggregation without release in a medium with both calcium and magnesium. When protein was omitted from the suspending medium, platelet aggregation in response to ADP was variable. In this medium, collagen and thrombin caused more extensive release than in the albumin-containing medium. Aggregation by polylysine was accompanied by release and extensive lysis in the protein-free medium. Thus, the composition of the final resuspending medium has a major effect on the responses of washed human platelets to aggregating agents.